Echoes from Mozambique: Did the idea of high modernism vanish? - Lars Buur; Thabit Jacob (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2024)
Mozambique has become a significant destination for a diverse portfolio of investments in mining, liquid natural gas, power plants, industrial complexes and large-scale agricultural schemes. Acquiring investments across sectors has re-emerged as a top national priority, though few of these projects are actually new. Most if not all of these grand plans were among the post-independence, MarxistLeninist, high-modernism and state-led development plans that were pursued in Mozambique in the 1970s and 1980s. Given that more or less identical plans from the 1970s are enjoying a resurgence currently, this article asks whether this means they are still embedded in ideas associated with highmodernism and grand ideas of social transformation? What characterizes today's plans in contrast to those of the heyday of the big state-led ideas about industry and infrastructural development that blossomed after independence in 1975? This article argues that the present attempts to implement investments are no longer embedded in the grand visions and ideas of social transformation that characterized high modernism, but are more concerned with creating opportunities for key constituencies in order to reproduce power. Present projects therefore come closer to the positions of illiberal modernizers by emphasizing modernization and transformative state-building in order to reproduce the authoritarian ruling Frelimo party while upholding idea semblance of formal liberal democracy.
Keywords: 330; Modernisierungstheorie; Entwicklungsplanung; Autoritarismus; Auslandsinvestition; Investition; Mosambik